Potential of Wood Harvesting Residues and Residual Stand Damage due to Timber Harvesting: A Case Study at PT Austral Byna in Central Kalimantan, Indonesia - Sona Suhartana; null Yuniawati; Seca Gandaseca; null Dulsalam; null Soenarno; Jegatheswaran Ratnasingam (International Journal of Forestry Research)
The practice of timber harvesting in natural forests which has been conducted up to now still leaves wood harvesting residue and residual stand damage. Most condition of wood harvesting residue is still good and can be utilized. The objective of this research was to determine the potency of wood harvesting residue and residual stand damage on timber harvesting in natural forests. The data on wood utilization, wood harvesting residue, and residual damage were collected from three sample plots. The sample plots were arranged in a systematic and purposive manner, and the data were processed with tabulation and average analysis. Research results showed that the average volume of wood being utilized was 9.212 m3 tree−1. The average volume of wood harvesting residues was 2.310 m3 tree−1, and the total average volume of wood harvesting residues which were good, defected, and broken was 2.121 m3 (80.952%), with an average volume for good wood harvesting residue condition of 1.038 m3 (34.808%). Proportions of wood harvesting residues were 2.154 m3 (94.444%) consisting of buttress as large as 0.102 m3 (5.159%), stumps as large as 0.375 m3 tree−1 (23.597%), butt as large as 0.855 m3 (35.930%), and end part as large as 0.821 m3 (29.758%). The average number of trees with a diameter of 20 cm which were damaged due to felling and skidding was 5 trees ha−1 (5.40%) and 6 trees ha−1 (6.58%), respectively.